Intrapreneurial fit and misfit: Enterprising behavior, preferred organizational and open innovation culture - Nick Chandler; Zoltán Krajcsák (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
In challenging times, the need for innovation is heightened and stems from employees who exhibit intrapreneurial characteristics. Not every corporate culture is a suitable environment for intrapreneurial behavior. This study examines the relationship between potential entrepreneurial behavior and preferred culture type. Through a principal component analysis of a sample of 1056 university students, four principal components of enterprising behavior (and roles) are found: Planning on results (project manager); Bearing the burden (pressure bearer); Innovating for others (innovating showstopper); and Learning from mistakes (experimental learner). Using the Organizational Culture Assessment Instrument, a linear regression analysis was conducted of culture types against components. A combination of strong inverse and direct relationships are found between these components and culture types (clan, market, adhocracy, and hierarchy). The findings help practitioners understand how existing culture will inhibit or encourage enterprising behaviors, with potential benefits in recruitment and selection, reductions in staff turnover and increases in innovation potential. The findings also indicate a need for reconsideration of the employer brand when attracting intrapreneurs.
Keywords: 650; characteristics; fit; intrapreneur; organizational culture